Usage patterns of paracetamol in France - Duong, Mai (Br J Clin Pharmacol, 2016)
AIMS: The aim of the present study was to describe the real‐life usage patterns of paracetamol. METHODS: The Echantillon Généraliste de Bénéficiaires (EGB) database, the permanent 1/97 representative sample from the French national healthcare insurance system, was searched in 2011 to identify usage patterns, concomitant chronic diseases and use of cardiovascular medication in users prescribed single‐ingredient (SP) and combination (CP) paracetamol, representing 85% of all sales. RESULTS: Of 526 108 subjects aged ≥15 years in the EGB, 268 725 (51%) had paracetamol dispensed on ≥1 occasion; of these, 207 707 (77%) were dispensed only SP and 61 018 (23%) received CP with or without SP. SP users were younger (48.3 years vs. 50.5 years), and 57% of SP users vs. 58% of CP users were female. Chronic comorbidities were more common in CP than SP users. SP users had, on average, 3.4 dispensings per year vs. 5.0 for CP users, for 36 defined daily doses (DDD, 3 g) of SP vs. 53 DDD per year for CP; 49% SP users bought 14 DDD or fewer; 15% bought >60 DDD. Use of paracetamol increased with age from about 16 DDD per year in 15–30‐year‐olds to over 90 DDD per year in patients above the age of 75; 53% of patients ≤60 years bought fewer than 14 DDD per year, whereas 55% of those >60 bought more than 30 DDD per year. More than half the dispensings exceeded the legal per‐box limit of 8 g. CONCLUSIONS: Over 50% of the French adult population were dispensed paracetamol at least once over the course of a year, generally for short‐term use. Considering recent misgivings on the real efficacy and safety of paracetamol, such widespread use might have important public health consequences.